Perioperative intravenous immunoglobulin treatment in a patient with severe acquired von Willebrand syndrome: case report and review of the literature. Issue 5 (30th March 2017) - Jennes, Eva; Guggenberger, Dorothee; Zotz, Rainer; Thompson, Lora; Brümmendorf, Tim H.; Koschmieder, Steffen; Jost, Edgar
Key Clinical Message: Acquired von Willebrand syndrome may be related to plasma cell dyscrasia and can cause severe bleeding complications. Treatment, for example, with intravenous immunoglobulins may be indicated in selected cases. Physicians treating plasma cell dyscrasia have to be aware of bleeding complications in these patients, and clarification is necessary. Abstract : Acquired von Willebrand syndrome may be related to plasma cell dyscrasia and can cause severe bleeding complications. Treatment, for example, with intravenous immunoglobulins may be indicated in selected cases. Physicians treating plasma cell dyscrasia have to be aware of bleeding complications in these patients, and clarification is necessary.